A correction method of elastic modulus in compression tests for linear hardening materials. (21st December 2015) - Liu, Wei; Huan, Yong; Dong, Jie; Dai, Yujing; Lan, Ding
Abstract: Abstract : A correction method for linear hardening materials is brought forward to obtain the true (or nearly true) modulus of cylindrical specimens with middle aspect ratios in compression tests. By considering the stress concentration near the interface between the specimen and the compression platen caused by slanted contact, a "sandwich" model is developed. A correction formula is derived and all parameters can be obtained from the tested stress–strain curve. Experiments were performed on Al 2024 specimens with four aspect ratios. The corrected results are closer to the intrinsic modulus than the tested values, which verify the effectiveness of the correction method.